Uma proposta de matriz de Referência em Ciência Tecnologia e Sociedade (CTS) para análise de vídeos de ensino de ciências no canal YouTube. - Souza, Juliana Bezerra de (2018)
The use of technology in education has been expanded and videos of the YouTube channel can be one of the tools to be used by teachers with the purpose of presenting students, in a more interesting way, the content to be worked on. In view of the above, we aimed to create a reference matrix that can be used by science teachers for the analysis of YouTube channel videos. For the construction of this matrix, ten researchers in Science, Technology and Society (CTS), associates of the Interdisciplinary Nucleus of Studies and Research in CTS (NIEPCTS), on science videos chosen by them were analyzed. The researchers in their reports explained the reasons they chose the videos, how they believe they can be used in science lessons, what science content is covered in the video, and what CTS elements can be explored from the video. The reports were later analyzed based on the theoretical references of the area of Science Teaching and CTS and categorized from Bardin (2016). The categories created were allocated within the Nature of Science and Technology (NdC & T) being: Scientific Literacy, Argumentation and Critical Thinking.